BUDI DARMA’S “CHARLES LEBOURNE” AS REPRESENTATION OF MAN’S DARKSIDE AND WEAKNESS OF THE INNERSIDE: A STRUCTURAL ANALYSIS - Alviani Permata (Humaniora, 2013)
This research is to analyze a short story of Budi Darma’s short story anthology The People of Bloomington (1980). “Charles Lebourne” was chosen because storythemes1 in the text can be clearly analyzed by a structural perspective. A Structural analysis on a literary work thoroughly explains and exposes the linkages of elements and aspects of the work to form a whole meaning. By analyzing six Episodes in the story, this structural approach produces two structures. Structure I as the “Structure of Encounter” between the characters shows the process of how the two finally live together before separated for a long time. While Structure II as the “Structure of Inner-Conflict” reflects the innerconflict of man in opposing pain, misery, the weakness, and the dark sides as a human being by comparing how the characters treat each other showed in the episodes. Finally, “Charles Lebourne” is seen as a model of an anxious man pursuing his identity and interacting with others.